Perception Versus Reality: Estimated and Actual Online Content Consumption Comparisons and Relationships to Classroom Performance. Issue 4 (December 2018) - Richardson, Michael V.; Bliss, Rebecca; Welton, Wade; Papa, Evan
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Introduction: As students and faculty are increasingly becoming more comfortable with technology, physical therapy programs are using the flipped classroom (FC) to provide an environment more conducive to active and problem-based learning. Most literature on students in graduate level health care professional programs rely on subjective student report. To our knowledge, no studies have compared objective actual student consumption of online content to subjective student perception of online content consumption. Nor have studies explored the relationship between actual online content consumption and classroom performance. In this study, we compared estimated and actual online content consumption as well as its relationship to student performance. We hypothesized that students would inaccurately estimate online content viewing amounts and that a positive correlation would exist between online content consumption and student performance. Methods: Upon completion of a patient mobility training course, 46 year-one physical therapist students estimated their weekly online content consumption. In this cross-sectional study design, we compared these estimations with student usage data provided by an online learning management system. Additionally, we compared examination grades and overall course grades to average weekly viewing times. A Pearson's product moment correlation assessed the relationship between weekly viewing time and student performance. Discriminant ability of weekly viewing time was assessed with receiver operating characteristic curve analyses. Results: At least 40% of the students overestimated their online consumption. Students overestimated their weekly viewing by 63.2%. Weekly viewing time was correlated with percentile class ranks. Discussion and Conclusion: Students chronically overestimated online content consumption. Physical therapy faculty should be aware of discrepancies between objective actual and subjective perceived consumption of online content and may consider implementing an open feedback loop relative to actual preparation for the FC since this study also found a positive relationship between weekly viewing time and student performance.